Emilio Aguinaldo under American and Japanese Rule: Submission for Independence? - Ara, Satoshi (Archīum Ateneo, 2015)
Some historians are skeptical of Emilio Aguinaldo’s heroism after his role in the Philippine revolution against Spain and the Philippine–American War in large part because of his apparent collaboration with the Americans and the Japanese. Actually little is known about events in Aguinaldo’s life after 1899. Thisarticle aims to shed light on the obscured periods in Aguinaldo’s life and career. In doing so, it addresses the questions: How could he have desired Philippine independence despite his submission to two imperial powers, America and Japan? Why did he collaborate with both powers? How would his place in Philippine history be evaluated?KEYWORDS: COLLABORATION, AMERICAN COLONIALISM, JAPANESE OCCUPATION, ASIA–PACIFIC WAR, ARTEMIO RICARTE